War, migration and modernity: The micro-politics of the Hijab in Northeastern Sri Lanka - Rapti Siriwardane (University of Bonn, Center for Development Research (ZEF), 2014)
Since 2009, Sri Lanka's formative post-war years have increasingly been coloured by the intensification of militant Sinhala-Buddhist movements. In particular, the popularisation of costumes such as the abaya and variants of the hijab were often instrumentalised as a discursive battlefield, in agitating against what was framed as constituting a rising tide in Middle Eastern Islamic radicalism. This paper reveals how majoritarian ethno-nationalist discourses have served to erase or flatten nuances with respect to ongoing "veiling" practices. In particular, it explores how diverse women articulate motivations governing their more recent adoption of the abaya in the context of radicalised social othering. With its focus on the conflict-affected northeast that is home to a significant number of Sri Lanka's "east coast Muslims", the study draws upon diverse costuming practices as a lens to interrogate the gendered politics of ethno-religious difference and post-war nationhood. It reveals how socio-economic and political transformations during wartime, coupled with experiences of transnational labour migration and the democratisation of women's formal education, lent the abaya a multiplicity of symbolic meanings and quotidian practices, which at times were seen to transcend faith-based sensibilities. It is argued that while meanings around spiritual piety and socio-moral propriety are often presented as a false dichotomy in expressing motivations around veiling, their conceptual distinctions remain compellingly real and are often tactically invoked by diverse women in negotiating the intensely militarised, class and gender-stratified spaces of the northeast. The paper draws upon ethnographic fieldwork conducted in the District of Trincomalee, Sri Lanka during the first quarter of 2013.
Keywords: 330; Everyday costume culture; nationalism; social identities; postwar Sri Lanka